Pengaruh Jenis dan Konsentrasi Pupuk Organik Cair terhadap Pertumbuhan Bibit Alpukat - Nadya Luthfiah Hidayati; Rusmana Rusmana; Ratna Fitry Yenny; Endang Sulistyorini (Jurnal Ilmiah Membangun Desa dan Pertanian, 2024)
Avocado is one of the plants that can produce crops in tropical countries and is one of the preferred fruit types by Indonesian people. The avocado type grown in Indonesia is the YM Avocado, which is endemic to Lebak. The YM avocado plant is still unknown to the Indonesian public or at least not very popular among them. This is because there is limited access to avocado seedlings and poor avocado growing practices. In the end, there is a need to develop better ways of avocado farming that include proper nutrition. This research bears the following objectives: To analyze the growth performances of avocado seedlings (Persea americana Mill) and the role of different types and concentrations of liquid organic fertilizer (LOF). The study was done from February to April 2024 at the Experimental Field, Faculty of Agriculture Sultan Ageng Tirtayasa University Kp. Cikuya Karang Kitri, Sindangsari Village Pabuaran District Serang Regency, Banten. The experimental design used in the study was a factorial Randomized Block Design, RBD, with two factors and three replications. The first factor was the type of LOF, which was further divided into two groups: banana peel LOF and banana stem LOF. The second factor was LOF. It had five levels, and there were five treatments: 0 mL/L water, 80 mL/L water, 160 mL/L water, 240 mL/L water, and 320 mL/L water. Treatment had three groups of plants, and each was given different treatments. There were 30 plants, and they were used as samples. The observation parameters constituted height increase in seedlings, number of leaves, length of leaves, size of the leaf area, and diameter of stem, respectively. The effect was highly significant at p < 0.05, and the result revealed that the banana stem LOF treatment positively impacted the stem diameter parameter, and from the result obtained above, banana stem LOF recorded the best average of 1.09 cm. The potential existed for an interaction between the type of banana peel LOF and the concentration of 320 mL/L water on the seedling height increase parameter.